Asymmetric Iridium Catalyzed C-C Coupling of Chiral Diols via Site-Selective Redox-Triggered Carbonyl Addition - Shin, Inji (Top Curr Chem, 2016)
Cyclometalated π-allyliridium C,O-benzoate complexes modified by axially chiral chelating phosphine ligands display a pronounced kinetic preference for primary alcohol dehydrogenation, enabling highly site-selective redox-triggered carbonyl additions of chiral primary-secondary 1,3-diols with exceptional levels of catalyst-directed diastereoselectivity. Unlike conventional methods for carbonyl allylation, the present redox-triggered alcohol C-H functionalizations bypass the use of protecting groups, premetalated reagents, and discrete alcohol-to-aldehyde redox reactions.